THE ROLE OF TECHNOLOGY IN IMPROVING THE QUALITY OF EDUCATION IN REMOTE AREAS - Dewi Kartika Sari; Suhana Sarkawi (Adisam Publisher, 2025)
The use of technology has great potential to improve the quality of education in remote areas. With the presence of the internet and digital devices, students and teachers can access various global educational resources, such as subject matter, digital books, and online courses. Technology also enables continuous training and support for teachers through e-learning platforms and webinars, so that they can update teaching methods according to student needs. However, the application of this technology requires adequate infrastructure and supporting policies. Collaboration between the government and relevant parties is essential to ensure equal access to the internet and digital devices, in order to optimise the benefits of technology in education in remote areas.